Curcumin-Loaded Solid Lipid Nanoparticles Enhanced Anticancer Efficiency in Breast Cancer - Wenrui Wang; Tiantian Chen; Henan Xu; Baihui Ren; Xiaodan Cheng; Rongrong Qi; Haibo Liu; Yueyue Wang; Lei Yan; Sulian Chen; Qingling Yang; Changjie Chen (Molecules, 2018)
Curcumin (Cur) has been widely used in medicine, due to its antibacterial, anti-inflammatory, antioxidant, and antitumor effects. However, its clinic application is limited by its instability and poor solubility. In the present wok, curcumin was loaded into solid lipid nanoparticles (SLNs), in order to improve the therapeutic efficacy for breast cancer. The results measured using transmission electron microscopy (TEM) indicated that Cur-SLNs have a well-defined spherical shape; the size was about 40 nm with a negative surface charge. The drug loading and encapsulation efficiency in SLNs reached 23.38% and 72.47%, respectively. The Cur-SLNs showed a stronger cytotoxicity against SKBR3 cells. In vitro cellular uptake study demonstrated a high uptake efficiency of the Cur-SLNs by SKBR3 cells. Moreover, Cur-SLNs induced higher apoptosis in SKBR3 cells, compared to cells treated by free drug. In addition, Western blot analysis revealed that Cur-SLNs could promote the ratio of Bax/Bcl-2, but decreased the expression of cyclin D1 and CDK4. These results suggested that Cur-SLNs could be a potential useful chemotherapeutic formulation for breast cancer therapy.